2007
DOI: 10.1021/la700913m
|View full text |Cite
|
Sign up to set email alerts
|

Surface Tension-Driven Self-Folding Polyhedra

Abstract: We discuss finite element simulations and experiments involving the surface tension-driven self-folding of patterned polyhedra. Two-dimensional (2D) photolithographically patterned templates folded spontaneously when solder hinges between adjacent faces were liquefied. Minimization of interfacial free energy of the molten solder with the surrounding fluidic medium caused the solder to ball up, resulting in a torque that rotated adjacent faces and drove folding. The simulations indicate that the folding process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
136
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 147 publications
(139 citation statements)
references
References 29 publications
1
136
0
Order By: Relevance
“…2002;Syms et al 2003;Leong et al 2007;Mastrangeli et al 2009). Recent experiments have shown that elasto-capillary wrapping can be achieved using drop impact on millimetric and centimetric scales (Antkowiak et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…2002;Syms et al 2003;Leong et al 2007;Mastrangeli et al 2009). Recent experiments have shown that elasto-capillary wrapping can be achieved using drop impact on millimetric and centimetric scales (Antkowiak et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The positive initial slope indicates the assembly process for the part with an initial orientation angle between 0° and 90° is a nonspontaneous process. Leong et al [17] pointed out that, as the size of the part increases, the weight increases and gravitational forces begin to dominate over the surface tension forces. Given proper design of parts, solder/liquid, binding sites and the fluidic/air environment, the self-assembly of micro and nano scale parts can be spontaneous.…”
Section: Discussionmentioning
confidence: 99%
“…With proper agitation in the fluid environment, millimeter-sized parts can settle into the required orientations with the local minimum surface energy [10,16]. As noted by Leong et al [17], surface forces scale favorably with deceasing part sizes, and self assembly driven by surface tension has the potential for the assembly of micro-and nano-scale parts. As the weight of millimeter-scale parts increases, gravitational forces begin to dominate, thus potentially rendering the self-assembly nonspontaneous.…”
Section: Introductionmentioning
confidence: 98%
“…Human-made examples include self-assembly of mechanical structures (Mao et al, 2002); self-assembly of 3D polyhedra (Leong et al, 2007); and self-assembly of electronic circuits (James and Tour, 2005). Algorithmic work on selfassembly includes directed self-assembly (Grzelczak et al, 2010) and applications to nanofabrication (Ozin et al, 2009), as well as research into autonomous self-repairing/differentiating systems on a Cell Matrix (Macias and Athanas, 2007).…”
Section: Self-assemblymentioning
confidence: 99%